2011
DOI: 10.1161/circheartfailure.111.962142
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Continuous-Flow Versus Pulsatile-Flow Left Ventricular Assist Devices on Myocardial Unloading and Remodeling

Abstract: Background Continuous-flow left ventricular assist devices (LVAD) are increasingly used for patients with end-stage heart failure (HF). We analyzed the effects of ventricular decompression by continuous- versus pulsatile-flow LVADs on myocardial structure and function in this population. Methods and Results Sixty-one patients who underwent LVAD implantation as bridge-to-transplant were analyzed (pulsatile-flow LVAD: Group P, n=31; continuous-flow LVAD: Group C, n=30). Serial echocardiograms, serum levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(87 citation statements)
references
References 35 publications
5
81
0
1
Order By: Relevance
“…22 Similar to SLAM, dP/dt has been shown to improve by increasing upon CF-LVAD implanta- tion. 8 Regardless of the cause of cardiomyopathy, a high LVEDP and weak contractile function culminate in ineffective unloading, which is consistent with the delayed-closure physiology of the mitral valve observed in M-mode echocardiography, and which in this study was quantified as the SLAM.…”
Section: A B C D Esupporting
confidence: 82%
See 3 more Smart Citations
“…22 Similar to SLAM, dP/dt has been shown to improve by increasing upon CF-LVAD implanta- tion. 8 Regardless of the cause of cardiomyopathy, a high LVEDP and weak contractile function culminate in ineffective unloading, which is consistent with the delayed-closure physiology of the mitral valve observed in M-mode echocardiography, and which in this study was quantified as the SLAM.…”
Section: A B C D Esupporting
confidence: 82%
“…Even in circumstances in which accurate Doppler evaluation is possible, some studies in CF-LVAD patients have revealed that, although E/e′ ratio decreases after LVAD implantation, it correlates poorly with invasive measurements of pulmonary capillary wedge pressure (PCWP). 7,8 Other guidelines are therefore needed to supplement current knowledge toward evaluating LV unloading and clinical status in CF-LVAD-supported patients.…”
Section: Left Ventricular Assist Device (Lvad)mentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with pulsatile LVADs, these newer devices produce a qualitatively different type of unloading (10,(12)(13)(14)(15). Large-scale trials that evaluated the clinical effectiveness of chronic continuous-flow LVAD unloading as a bridge to transplantation or destination therapy were primarily focused on morbidity, mortality and changes in end-organ function, and did not include evaluation of serial myocardial functional or structural data (1,2,(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%